Building Faculty Capacity through High-Impact Practices: The Eric Grosse Memorial Fellowship for Part-Time Faculty Development - Paul Miller; John Erik Swanson (Teaching and Learning Excellence through Scholarship)
Over the past 2 decades the role of part-time faculty in U.S. higher education has grown dramatically. Today, contingent instructors—most of them part-time—make up over half of the instructional workforce at American colleges and universities, and at community colleges they often account for 60-70% of the teaching staff (Center for Community College Student Engagement, 2014; Jaeger & Eagan, 2009). Despite their essential contributions to student learning, part-time faculty are frequently excluded from campus professional development programs, lack adequate institutional support, and are rarely integrated into the broader academic community (Kezar & Maxey, 2014). This gap not only undermines the professional growth and satisfaction of contingent faculty, but it also risks compromising student success, particularly for historically underserved student populations who disproportionately enroll in community colleges (Eagan & Jaeger, 2008).